A common variant of CNTNAP2 is associated with sub-threshold autistic traits and intellectual disability. - Yuka Shiota; Tetsu Hirosawa; Yuko Yoshimura; Sanae Tanaka; Chiaki Hasegawa; Sumie Iwasaki; Kyung-Min An; Daiki Soma; Masuhiko Sano; Shigeru Yokoyama; Mitsuru Kikuchi (PLoS ONE)
Sub-threshold autistic traits are common in the general population. Children with sub-threshold autistic traits have difficulties with social adaptation. Contactin-associated protein-like 2 (CNTNAP2) is associated with the development of Autism spectrum disorder (ASD) and the single-nucleotide polymorphism rs2710102 (G/A) of CNTNAP2 is suggested to contribute to sub-threshold social impairments and intellectual disabilities. We recruited 67 children with Autistic disorder (AD) (49 boys, 18 girls, aged 38-98 months) and 57 typically developing (TD) children (34 boys, 23 girls, aged 53-90 months). We assessed the participants' intelligence and social reciprocity using the Kaufman Assessment Battery for Children (K-ABC) and the Social Responsiveness Scale (SRS), respectively. Genomic DNA was extracted from the buccal mucosa and genotyped for rs2710102. A chi-square test revealed a significant association between genotype and group [χ2(2) = 6.56, p = 0.038]. When a co-dominant model was assumed, the results from linear regression models demonstrated that TD children with A-carriers (AA + AG) presented higher SRS T-scores [t(55) = 2.11, p = 0.039] and lower simultaneous processing scale scores of K-ABC [t(55) = -2.19, p = 0.032] than those with GG homozygotes. These associations were not significant in children with ASD. TD children with the rs2710102 A-allele may have more sub-threshold autistic traits than those with GG homozygotes, reflected in higher SRS scores and lower simultaneous processing scale scores. These results support the use of genetic evidence to detect sub-threshold autistic traits.